Hofstede's cultural dimensions: an insight to the practise of power distance in Malaysia / Etty Harniza Harun ... [et al.] - Harun, Etty Harniza; Abdul Rahim, Hasni; Mohamad Salleh, Musdiana (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
This paper provides an insight to the theory of Hofstede's cultural dimensions and how it gives effect to an organization's working culture. Discussions of the theory then further concentrated on one of the dimension that is the practise of power distance in Malaysia and how it specifically affect the working culture and the relationship between supervisor and the subordinates.